SUN-377 Efficacy of Low Dose Denosumab in Maintaining Bone Mineral Density in Postmenopausal Women with Osteoporosis: A Real World, Prospective Observational Study - Khan, Aliya Aziz (J Endocr Soc, 2020)
Introduction: Denosumab, a fully human monoclonal antibody to RANK-ligand, has been shown to increase bone mineral density (BMD) and reduce the risk of hip, vertebral and non-vertebral fractures in postmenopausal women with osteoporosis (1-3). Varying doses of denosumab including 30mg/3months have demonstrated a decrease in bone remodelling in a dose-dependent manner (2,4-6). The primary objective of this study is to evaluate the efficacy of low dose denosumab (30mg/6 months) in postmenopausal women with osteoporosis who are reluctant to consider or continue the full dose of denosumab due to adverse events (AE) or concerns of potential AE. Methods: Following informed consent, postmenopausal women with a T-score of ≤ -2.5 at the lumbar spine (LS) or at the total hip (TH) received denosumab 30mg/6months. Patients with an additional skeletal disorder, prior fragility fracture, or on oral steroids (daily in the past 12 months) were excluded. The primary endpoint was the percent change in BMD at the lumbar spine (LS), total hip (HP), femoral neck (FN) and 1/3 radius (1/3R) at 12 months. Secondary outcomes were 1) percent change in BMD at the LS, TH, FN, and 1/3R at 24 months and 2) AE. Results: We enrolled 183 patients. The mean age was 69 years (SD= 7.07), 80% of patients had a moderate fracture risk (CAROC tool), 3% were current smokers and 9% consumed alcohol daily. 14.4% of patients were on SSRI/SNRI, 9.6% were on PPI, and no patient was on an aromatase inhibitor. At 12 months (n=125), the mean BMD significantly increased by +2.0% (95% CI 2.8%-1.3%) at the LS (p<0.001). There was no significant change in BMD at the FN, TH, AND 1/3R. At 24 months (n=65), the percent change in BMD was +3.4% (95% CI 4.8%-2.0%: p<0.001) at the LS, +1.5% (95% CI 2.9%-0.15%: p=0.031) at the FN, +1.9% (95% CI 3.5%-0.24%: p=0.025) at the 1/3R. There was no significant change in BMD at the TH. Conclusion: Low dose denosumab appears to be effective in maintaining BMD in postmenopausal women with a moderate fracture risk and may be of benefit in individuals who are experiencing side effects or concerns of side effects. This may also be of value following 10 years of therapy in order to maintain BMD. References 1.Bekker, PJ, Holloway DL, Rasmussen AS, Murphy R, Martin SW, Leese PT... Depaoli AM. A Single-Dose Placebo-Controlled Study of AMG 162, a Fully Human Monoclonal Antibody to RANKL, in Postmenopausal Women. JBMR, 2004;19(7), 1059-1066. 2.Kumagai Y, Hasunuma T, Padhi D. A randomized, double-blind, placebo-controlled, single-dose study to evaluate the safety, tolerability, pharmacokinetics and pharmacodynamics of denosumab administered subcutaneously to postmenopausal Japanese women. Bone, 2011;49(5), 1101-1107. 3.Lewiecki EM, Miller PD, Mcclung MR, Cohen SB, Bolognese MA, Liu Y, . . . Fitzpatrick LA. Two-Year Treatment With Denosumab (AMG 162) in a Randomized Phase 2 Study of Postmenopausal Women With Low BMD. JBMR, 2007;22(12), 1832-1841.